Role of nasolacrimal duct probing in pre-operative endo-dacryocystorhinostomy - Munjal, Manish; Kaur, Amanjot; Singh, Akashdeep; Bajwa, G. S.; Munjal, Shubham; Bansal, Vasu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Infection s and facial trauma are likely to disrupt the lacrimal flow in the region of the medial canthus. Individuals with epiphora refractory to topical medication and secondary to an obstructive aetiology were subjected to nasolacrimal duct probing prior to endo-nasal-dacrocystorhinostomy, to identify the likely site of obstruction, cannalicular, common cannalicus or in the nasolacrimal duct. Methods: 40 adult subjects of long duration epiphora were selected from the outpatient clinics of otorhinolaryngology and opthalmology services of Dayanand Medical College and Hospital, Ludhiana. Results: On pre-operative lacrimal probing, the block was detected at a distance of greater than 3 cm in 26 sides (65%) and less than 3 cm in 14 sides (35%). Conclusions: In patients of epiphora, the naso-lacrimal system had an obstruction, in the duct and usually at a distance of greater than 3 cm from the punctum.